2020
DOI: 10.1001/jamanetworkopen.2020.29058
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors Associated With In-Hospital Mortality in a US National Sample of Patients With COVID-19

Abstract: IMPORTANCECoronavirus disease 2019 (COVID-19) has infected more than 8.1 million US residents and killed more than 221 000. There is a dearth of research on epidemiology and clinical outcomes in US patients with COVID-19. OBJECTIVES To characterize patients with COVID-19 treated in US hospitals and to examine risk factors associated with in-hospital mortality. DESIGN, SETTING, AND PARTICIPANTS This cohort study was conducted using Premier Healthcare Database, a large geographically diverse all-payer hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
372
7
20

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 416 publications
(456 citation statements)
references
References 25 publications
57
372
7
20
Order By: Relevance
“…Among death certificates from calendar year 2020 listing COVID-19 and at least one other co-occurring diagnosis, the documentation is consistent with these deaths being attributable to COVID-19. Specifically, in 97% of 357,133 death certificates with COVID-19 and at least one other diagnosis, the documented chain-of-event and significant contributing conditions were consistent with those reported in clinical and epidemiologic studies to occur among patients with severe COVID-19-associated outcomes (5,9). Only 5.5% of death certificates had COVID-19 without any other conditions listed.…”
Section: Discussionsupporting
confidence: 74%
“…Among death certificates from calendar year 2020 listing COVID-19 and at least one other co-occurring diagnosis, the documentation is consistent with these deaths being attributable to COVID-19. Specifically, in 97% of 357,133 death certificates with COVID-19 and at least one other diagnosis, the documented chain-of-event and significant contributing conditions were consistent with those reported in clinical and epidemiologic studies to occur among patients with severe COVID-19-associated outcomes (5,9). Only 5.5% of death certificates had COVID-19 without any other conditions listed.…”
Section: Discussionsupporting
confidence: 74%
“…While these findings need to be confirmed in a larger study cohort of ESKD patients, they seem to be consistent with later reports involving a big study population. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…To examine risk factors associated with in-hospital mortality in a US national sample of patients with COVID-19. Recently, in a cohort study, the result have reported that patients with both AZM and HCQ had increased odds of death than patients with no HCQ or AZM [ 27 ]. Furthermore, meta-analysis found that the mortality difference was not significant, neither in HCQ treatment group nor in HCQ plus AZM treatment group in comparison to controls [ 28 ].…”
Section: Overview Of Covid-19mentioning
confidence: 99%